September 2017's Geoeffective Space Weather and Impacts to Caribbean Radio Communications During Hurricane Response. Issue 9 (3rd September 2018) - Redmon, R. J.; Seaton, D. B.; Steenburgh, R.; He, J.; Rodriguez, J. V.
Abstract: Between 4 and 10 September 2017, multiple solar eruptions occurred from active region AR12673. NOAA's and NASA's well‐instrumented spacecraft observed the evolution of these geoeffective events from their solar origins, through the interplanetary medium, to their geospace impacts. The 6 September X9.3 flare was the largest to date for the nearly concluded solar cycle 24 and, in fact, the brightest recorded since an X17 flare in September 2005, which occurred during the declining phase of solar cycle 23. Rapid ionization of the sunlit upper atmosphere occurred, disrupting high‐frequency communications in the Caribbean region while emergency managers were scrambling to provide critical recovery services caused by the region's devastating hurricanes. The 10 September west limb eruption resulted in the first solar energetic particle event since 2012 with sufficient flux and energy to yield a ground level enhancement. Spacecraft at L1, including DSCOVR, sampled the associated interplanetary coronal mass ejections minutes before their collision with Earth's magnetosphere. Strong compression and erosion of the dayside magnetosphere occurred, placing geosynchronous satellites in the magnetosheath. Subsequent geomagnetic storms produced magnificent auroral displays and elevated hazards to power systems. Through the lens of NOAA's space weather R‐S‐G storm scales, this event period increased hazards for systems susceptible to elevated "radio blackout" (R3‐strong), "solar radiation storm" (S3‐strong), and "geomagnetic storm" (G4‐severe) conditions. The purpose of this paper is to provide an overview of the September 2017 space weather event, and a summary of its consequences, including forecaster, post‐event analyst, and communication operator perspectives. Key Points: The September 2017 solar events impacted high‐frequency radio links for ground and aviation communication Radio communications used in hurricane emergency and disaster relief management were affected, especially in the Caribbean Active region AR12673 released four X‐class flares, three coronal mass ejections, and a solar energetic particle event with ground level enhancement